Study of flexural response of engineered cementitious composite faced masonry structures. (1st November 2017) - Singh, S.B.; Patil, Richa; Munjal, Pankaj
Highlights: Flexural response of masonry beams strengthened with ECC sheets are investigated. The experimental results are validated numerically. Parametric study of flexural response of strengthened masonry beams has been done. Optimum thickness of ECC sheet and bonding agents are recommended. Abstract: This study aims to develop and demonstrate the effectiveness of precast engineered cementitious composite (ECC) plates for strengthening of masonry beams by bonding them on tension face as well as both on tension and compression faces like sandwich beam. Two types of bonding materials have been used, i.e., epoxy and cement mortar for bonding the ECC plates with masonry beam. Experimental flexural response has been predicted for tension strengthened as well as sandwich beams. Detailed parametric study has been performed using ABAQUS commercial software package. The parametric study incorporates the effect of various parameters such as ECC thickness in compression and tension, epoxy and cement mortar as bonding agents, and bonding agent thickness on the flexural response of strengthened beams. All beams were tested under four-point loading systems. The numerical results obtained using ABAQUS are validated with experimental results. The present study results reveal that the application of precast ECC increases the strength and deformability of masonry beams and hence demonstrate its effectiveness as strengthening element for masonry structures. Furthermore, recommendations regarding optimum thickness of ECC strips/plates and bonding agents have been made for external strengthening of masonry beams with precast ECC strips.